Peran Ulama dalam Pengembangan Islam di Nusantara serta Membangun Kebersamaan dan Keadilan Sosial - Yasin, Nur Ali; Wulandari, Eka Pratiwi; Ufairah, Raisah (TAMADDUN: Jurnal Ilmu Sosial, Seni, dan Humaniora, 2025)
This article discusses the contribution of ulama in the development of Islam in the archipelago and creating social justice in society by tracing the historical, cultural, and intellectual roles of ulama in the context of Islam Nusantara. Ulama not only act as spiritual leaders and guardians of Islamic teachings, but also as agents of social change who contribute to creating harmony, building educational institutions, developing Islamic thought, and becoming political advisors and defenders of the marginalized. With a qualitative approach through literature study, this article reveals how ulama Nusantara succeeded in linking Islamic values ​​with local culture and participated in fighting for social justice through scientific movements, the establishment of Islamic boarding schools, advocacy for community rights, and strengthening the role of female ulama in the contemporary context. The results of the study show that the role of ulama is very significant in forming an inclusive and just social structure in a multicultural society. This article emphasizes the importance of revitalizing the role of ulama in responding to contemporary social challenges in order to create a just, prosperous, and civilized society.